GE_GERICHTE P/18997/2021 vom 24. Juli 2024 - GE Cour de justice (2024)
IN DUBIO PRO REO;DISPOSITIONS PÉNALES DE LA LEI;COAUTEUR(DROIT PÉNAL);INTENTION | LEI.11; LEI.91.al1; LEI.117.1; CP.29; CP.12.al2